Moxifloxacin Susceptibility Mediates the Relationship between Causative Organism and Clinical Outcome in Bacterial Keratitis - Oldenburg, Catherine E. (The Association for Research in Vision and Ophthalmology, 2013)
PURPOSE. Bacterial keratitis is a sight-threatening infection of the cornea that is one of the leading causes of blindness globally. In this report, we analyze the role of moxifloxacin susceptibility in the relationship between causative organisms and clinical outcome in bacteria keratitis. METHODS. A mediation analysis is used to assess the role of moxifloxacin susceptibility in the relationship between causative organisms and clinical outcome in bacterial keratitis using data collected in a randomized, controlled trial. RESULTS. In the Steroids for Corneal Ulcers Trial (SCUT), 500 corneal infections were treated with topical moxifloxacin. The outcome of 3-week best spectacle-corrected visual acuity was significantly associated with an organism (Streptococcus pneumoniae, Pseudomonas aeruginosa, etc., P = 0.008). An indirect effects mediation model suggests that MIC accounted for approximately 13% (95% confidence interval, 3%–24%, P = 0.015) of the effect of the organism on 3-week visual acuity. CONCLUSIONS. Moxifloxacin mediates the relationship between causative organisms and clinical outcome in bacterial keratitis, and is likely on the causal pathway between the organism and outcome. (ClinicalTrials.gov number, NCT00324168.)